Voters’ responsiveness to public employment policies - Curto-Grau, Marta (Public choice, 2017)
This paper examines the electoral rewards for the distribution of public employment. We focus on the Spanish Plan for Rural Employment, a public jobs program introduced by the central government in two lagging regions. We evaluate voters’ responsiveness to this policy using municipal-level electoral data and employ an estimator that combines difference-in-differences with propensity score matching. The main ﬁndings are that the program lead to an increase in the vote share for the ruling party in the treated municipalities. This effect is very persistent over the years, and it is unlikely to be explained by turnout buying.